The Legal-Economic Nexus from the Perspective of New Institutional Economists and Original Institutional Economists. Issue 2 (3rd April 2018) - Spithoven, Antoon
Abstract: There are two institutional economics approaches to law and economics. New institutional economists prescribe that arbitrators foster efficiency in setting economic disputes and original institutional economists focus on creating reasonable values – that is, balancing efficiency and justice. Disequilibrium between desired efficiency and perceived fairness triggers agency and is a source of coevolution of law and economics.